2017
DOI: 10.2215/cjn.12921216
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Prevalence and Associations of Limited Health Literacy in CKD

Abstract: Limited health literacy is common in CKD, especially among individuals with low socioeconomic status and nonwhite ethnicity. This has implications for the design of self-management and decision-making initiatives to promote equity of care and improve quality. Lower prevalence among patients with transplants may reflect selection of patients with higher health literacy for transplantation either because of less comorbidity in this group or as a direct effect of health literacy on access to transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
128
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(140 citation statements)
references
References 62 publications
(131 reference statements)
3
128
1
8
Order By: Relevance
“…; Taylor et al . ). To address potential barriers to sensemaking and difficulties with the interpretation and application of the renal diet that may be due to inadequate health literacy, we recommend incorporating several rounds of teachback (Dinh et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Taylor et al . ). To address potential barriers to sensemaking and difficulties with the interpretation and application of the renal diet that may be due to inadequate health literacy, we recommend incorporating several rounds of teachback (Dinh et al .…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the complexity of the diet, patients and carers in the current study described receiving renal diet information that was confusing and contradictory. Some of the difficulties experienced by patients when interpreting messages on diet sheets, could be attributed to the high level of cognitive impairment in patients with CKD (Lambert et al 2016); as well as low health literacy experienced among this patient population (Lambert et al 2015;Taylor et al 2017). To address potential barriers to sensemaking and difficulties with the interpretation and application of the renal diet that may be due to inadequate health literacy, we recommend incorporating several rounds of teachback (Dinh et al 2016) during education sessions to evaluate recall, and to ascertain understanding of important or complex concepts (Gibbs & Chapman-Novakofski 2012;Negarandeh et al 2013;Dantic 2014;Porter et al 2016;Gibbs 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the studies in this review touched on concepts related to health literacy, such as language and culture, they did not discuss low health literacy specifically as being a barrier to access in this population group. However, it is known from the literature that people from diverse cultural and linguistic backgrounds and those who are experiencing socioeconomic disadvantage are more likely to have low health literacy [28] and be less engaged with self-management [29]. Low health literacy in patients is associated with poorer patient health outcomes, poorer medication adherence and poorer knowledge and understanding of their own condition.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prior studies have shown that limited health literacy is common among patients with CKD and is associated with inferior outcomes including decreased likelihood of undergoing kidney transplantation. [18][19][20] Alternatively, it may be reflective of the residual role of peritransplant financial hardship as a barrier to receiving the long-term benefits of transplantation for some patients. [21][22][23] Regardless, this group-level heterogeneity in participant responses demonstrates that the development of effective, comprehensive informational materials requires the input of all segments of the diverse CKD/ESRD population (including, perhaps, those who were denied the opportunity to be transplanted).…”
Section: More Than 19 000 Patients Receive Kidney Transplants In the mentioning
confidence: 99%